(untitled) (The Pakistan Development Review, 1997)
The main objective of this paper has been to review Pakistan’s historical experience in agricultural development in terms of growth, income distribution, and rural poverty. While the long-term growth rates between 1949-50 and 1994-95 were satisfactory, the variations around the average have been rather too large over the various decades. Beginning with a stagnating sector of the 1950s, agriculture witnessed record growth rates during the Sixties. This was followed by the lowest growth rates of the early Seventies, and acceleration in the second half of the Seventies. The experience since 1979-80 has been mixed, but the growth rates have been rather low through the Eighties and the Nineties. The trends in income distribution and poverty varied directly in relation to the agricultural growth rates, especially when they were in excess of the threshold level of 4.5–5.0 percent per annum. In general, a growth rate of 5.0 percent or higher has induced positive changes in income distribution and poverty. In view of this positive association, the pursuit of a high growth policy in agriculture should guide Pakistan’s future development strategy. The efficiency of resource use, a greater dependence on modern technologies, and a minimisation of government intervention in the market mechanism are the essential pillars of the high growth strategy.